2018
DOI: 10.1158/1055-9965.epi-17-1023
|View full text |Cite
|
Sign up to set email alerts
|

The Sun Solutions Intervention for Operating Engineers: A Randomized Controlled Trial

Abstract: Because Operating Engineers (heavy equipment operators) are outdoor workers at risk for skin cancer, interventions are needed to promote sun safety. The objectives were to determine changes in sunscreen use and sunburning among Operating Engineers randomized to four conditions in the Sun Solutions study: (i) education only; (ii) education and text message reminders; (ii) education and mailed sunscreen; and (iv) education, text message reminders, and mailed sunscreen. In this randomized controlled trial, Operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 56 publications
2
40
0
1
Order By: Relevance
“…Seven studies assessed the acceptability and satisfaction with education programmes and found that the majority of participants rated them positively (also see Table ).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Seven studies assessed the acceptability and satisfaction with education programmes and found that the majority of participants rated them positively (also see Table ).…”
Section: Resultssupporting
confidence: 82%
“…Four studies assessed sun‐related attitudes, of which three found significant differences in the sun risk attitude and perceived sun damage susceptibility . Sixteen studies found a significant protective behavioural changes and two studies reported significant changes in the intention to change sun protection behaviour …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations